Comparison of Microeconomics and Stock Returns Relationships in Financial Sector in 2019 and 2020 - Mei Siang Jemima Aurelia; Edwin Setiawan Nugraha (Jurnal Keuangan dan Perbankan, 2022)
Stock return is crucial to analyze before making investment since gaining return is the main objective. The analyzing can implement fundamental analysis which involves microeconomics variables of company. According to IDX, financial sector generates the highest return, unfortunately it is still volatile. Moreover, since COVID-19 pandemic, economic situation becomes unstable. This research aims to analyze and compare partial and simultaneous relationship of microeconomics variables (Book Value Per Share, Price to Book Value, Price Earning Ratio, Debt to Equity Ratio, Net Profit Margin and Debt Ratio) with stock return in financial sector main board companies in 2019 (before COVID-19 pandemic) and 2020 (during COVID-19 pandemic). Multiple linear regression is implemented and resulting that in 2019, only Price to Book Value, Price Earning Ratio and Net Profit Margin have significant relationship with stock return. In 2020, only Price Earning Ratio and Debt to Equity Ratio have significant relationship with stock return. For both years, simultaneous relationship between all microeconomics variables and stock return are found. The result can be used for investor and main board financial sector companies.